Mating under climate change: Impact of simulated heatwaves on the reproduction of model pollinators - Martinet, Baptiste; Zambra, Ella; Przybyla, Kimberly; Lecocq, Thomas; Anselmo, Abigaël; Nonclercq, Denis; Rasmont, Pierre; Michez, Denis; Hennebert, Elise; Pum Lee, Kwang (Functional ecology, 2021)
Climate change is related to an increase in frequency and intensity of extreme events such as heatwaves. It is well established that such events may worsen the current world‐wide biodiversity decline. In many organisms, heat stress is associated with direct physiological perturbations and could lead to a decrease of fitness. In contrast to endotherms, heat stress resistance has been poorly investigated in heterotherms; especially in insects, in which the internal physiological mechanisms available to regulate body temperature are almost negligible making them sensitive to extreme temperature variations. Wild bees are crucial pollinators for wild plants and crops. Among them, bumblebees are experiencing a strong decline across the world. Therefore, the ongoing global decline of these insect pollinators partly due to climate change could cause major economic issues. Here we assess how simulated heatwaves impact fertility and attractiveness (key parameters of sustainability) of bumblebee males. We used three model species: Bombus terrestris, a widespread and warm‐adapted species, B. magnus and B. jonellus, two declining and cold‐adapted species. We highlight that heat shock (40°C) negatively affects sperm viability and sperm DNA integrity only in the two cold‐adapted species. Heat shock can also impact the structure of cephalic labial glands and the production of pheromones only in the declining species. The specific disruption in key reproductive traits we identify following simulated heatwave conditions could provide one important mechanistic explanation for why some pollinators are in decline through climate change. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.